Comparative Analysis of Green Accounting Practices in Lombok’s Property Sector: Challenges and Profitability Implications - Yusli Mariadi; Nungki Kartikasari; Robith Hudaya; Yeldy Dwi Genadi (Cita konsultindo, 2024)
Green accounting integrates social and environmental costs into financial reports. This study evaluates its application in two Lombok property companies, PT Nata Alam Raya and PT Meka Asia Properti. Using semi-structured interviews and audited financial statement analysis, the study finds PT Meka Asia Properti more proactive in sustainability promotion, though neither company formally integrates green accounting. Key challenges include insufficient regulations mandating environmental and social cost disclosure and high implementation costs.